INVESTIGATIONS OF THIN TITANIUM OXIDE FILMS GROWN BY REACTIVE PULSED LASER DEPOSITION - Gabriela Dorcioman; Oana Fufa; Valentin Craciun; Marimona Miroiu; Petronela Garoi; Emanuel Axente; Felix Sima; Doina Craciun (Romanian Society of Oral Rehabilitation, 2018)
Titanium oxide thin films were deposited on Si monocrystalline substrate using the pulsed laser ablation technique in a reactive oxygen atmosphere. The films were obtained starting from Ti and TiO2 targets which were ablated using a KrF* excimer laser (λ = 248 nm). During the deposition, the Si substrates were heated at 300 °C under various high purity oxygen atmosphere of 1.0, 0.5 and 0.1 mbar. Grazing incidence X-ray diffraction investigations revealed the presence of a nanostructured film consisting of a mixture of several titanium oxides, with crystalline grains size of few nm to 10 nm. Only the film deposited from the Ti target at a pressure of 1.0 mbar exhibited crystalline grains of 30-40 nm. Thin films surface morphology and topography, studied using atomic force and scanning electron microscopy, revealed a relatively smooth surface with the presence of some submicron droplets, typical for laser ablation technique. Films deposited at 0.5 mbar pressure from both targets were significantly rougher than the other deposited films